Nodal modulation of M2 and N2 tides along the Norwegian coast - Zong, Xiaolong; Zhou, Jun; Yang, Minghui; Zhang, Shuwen; Deng, Fangjing; Lian, Qiang; Zhou, Wei; Chen, Zhaoyun (Frontiers in Marine Science, 2024)
It is crucial to assess the nodal modulation for tides in high-latitude coast areas within the context of global warming. In this paper, five stations (Maloy, Rorvik, Andenes, Vardo, and Honningsvag) along the Norwegian coast are selected to analyze the nodal modulation using the S_TIDE toolbox, which is developed from the enhanced harmonic analysis method. Three criterions are proposed to determine the optimal number of independent points (IPs), a parameter in S_TIDE toolbox, and the decision steps are elaborated in detail. The optimal number of IPs is evaluated by comparing the primary and the hindcasts tidal amplitudes. The amplitudes of 18.61-year cycle and 4.42-year cycle show noticeable temporal and spatial variations, which can be attributed to the changes of sea levels, local topography, and the active and robust mesoscale activity in the Norwegian Sea. Moreover, the temporal and spatial variations in nodal modulation are quantitatively demonstrated at the Rorvik and Vardo stations, highlighting the importance of nodal modulation in assessing tides over interdecadal periods.